Analysis Of The Mediating Role Of Service Quality On The Influence Of Employee Communication Competence And Price On Customer Satisfaction - M. Ivan Dwi Septiyan; Rifky Ardhana Kisno Saputra; Arief Sundari (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The existence of Small and Medium Enterprises (SMEs), particularly in the coffee shop sector, is significantly influenced by customer satisfaction levels. This research aims to analyze the influence of employee communication competence and price on customer satisfaction, with service quality as a mediating variable at Warung Kopi Sekar Jagad in Tuban Regency. The study adopts a quantitative associative methodology. Data are collected through structured questionnaires distributed to customers using accidental sampling techniques. The data analysis is performed using Path Analysis to examine both direct and indirect effects within the research model. The findings indicate that employee communication competence and price significantly influence service quality. Furthermore, service quality has a significant impact on customer satisfaction and serves as a vital mediator that links communication competence and price to overall satisfaction levels. In conclusion, to enhance customer satisfaction, SMEs must prioritize improving communication skills among staff and maintaining competitive pricing policies, both of which are manifested through superior service quality.